1996
DOI: 10.1046/j.1471-4159.1996.66052197.x
|View full text |Cite
|
Sign up to set email alerts
|

A Hydrophilic Peptide Comprising 18 Amino Acid Residues of the Prosaposin Sequence Has Neurotrophic Activity In Vitro and In Vivo

Abstract: Prosaposin, a 51 7-amino-acid glycoprotein, not only acts as the precursor ofsaposin A, B, C, and 0 but also possesses neurotrophic activity to rescue hippocampal CAl neurons from ischemic damage in vivo and to promote neurite extension of neuroblastoma cells in vitro. Recently, the trophic activity of prosaposin on human neuroblastoma cells has been shown to reside in the NH 2-terminal hydrophilic sequence (LIDNNRTEEILY) of the human saposin C. Here we show that prosaposin, saposin C, and a peptide comprising… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(58 citation statements)
references
References 15 publications
3
55
0
Order By: Relevance
“…Saposin C contains a neurotrophic peptide (54)(55)(56) that is present in mammalian but not in chicken prosaposin (47) or in J3-crystallin (present study), suggesting a later evolutionary development. This active peptide, called prosaptide, acts as a Schwann-cell survival factor via a phosphorylation signaltransduction pathway associated with myelin formation (57)(58)(59).…”
Section: Discussionmentioning
confidence: 48%
“…Saposin C contains a neurotrophic peptide (54)(55)(56) that is present in mammalian but not in chicken prosaposin (47) or in J3-crystallin (present study), suggesting a later evolutionary development. This active peptide, called prosaptide, acts as a Schwann-cell survival factor via a phosphorylation signaltransduction pathway associated with myelin formation (57)(58)(59).…”
Section: Discussionmentioning
confidence: 48%
“…Prosaptide is a peptide fragment that mimics the trophic and protective actions of full-length prosaposin (23,24,26,28,32,35,36,38,53,54), but it is widely presumed that full-length prosaposin is the endogenous ligand for any receptor that can be activated by prosaptide. Thus, we purified full-length prosaposin using a slightly modified version of a previously described protocol (58) and assessed whether full-length prosaposin could activate GPR37 and GPR37L1.…”
Section: Resultsmentioning
confidence: 99%
“…It was demonstrated that prosaposin possesses a strong protective action against ischemic damage to hippocampal neurons when infused intracerebroventrically before ischemia (Sano et al, 1994), suggesting that prosaposin may be neurotrophic in action. It is further suggested that the in vitro and in vivo trophic actions of prosaposin on hippocampal and cortical neurons are related to a linear 18-mer prosaposin-derived peptide (18MP: LSELIINNATEELLIKGL) comprising the hydrophilic sequence of the rat saposin C domain (Kotani et al, 1996). However, the role of 18MP in molecular mechanisms of ischemia-induced neuronal degeneration remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%